Joint investment on resilience of cross-country transport infrastructure - Zheng, Shiyuan; Chen, Xirong; Dong, Kangyin; Wang, Kun; Fu, Xiaowen (Transportation research. Part A, Policy and practice, 2022)
•We examine the joint resilience investment on the cross-country transport infrastructure.•The first-best outcomes can be achieved if the resilience investment is verifiable.•The non-verifiability leads to a downward distortion on investment under higher disruption.•The first-best outcomes can still be achieved under non-verifiability if the disruption is low. Unlike the domestic transport infrastructure, the cross-country ones are subject to more diverse and unconventional disruption risks due to the unstable geopolitical conditions, terrorist attacks, and complex landscape and extreme weather events, thus calling for resilience-related investments from different countries. However, such resilience investment made by one country to deal with such unconventional disruption risk is very hard to be verified by other countries (i.e., non-verifiability). This paper establishes an integrated economic model to analytically examine countries’ joint resilience investments on the cross-country transport infrastructure in presence of non-verifiability. Specifically, there is one “investing country” who constructed the infrastructure which is also used by a “host country”. Our analytical results suggest that the first-best investment and market outcomes for the global welfare maximization can be achieved if the resilience investment is verifiable. The non-verifiability is, however, found to cause a downward distortion in the resilience investment and an upward distortion in transport price when the probability of the disruption is higher such that the resilience investment only partially covers the potential loss. On the contrary, when the probability of disruption is low so that the resilience investment can lead to the full loss coverage, the first-best outcomes can still be achieved without any distortion. Our analytical model is also extended to account for the intermodal competition. Although our main conclusions still qualitatively hold, the intermodal competition is found to have uncertain effects on the market outcomes, depending on the interaction between the resilience investment cost and the degree of the intermodal competition.